Peran Platform Weverse Sebagai Sarana Interaksi Dan Ekonomi Dalam Industri K-Pop - Ciek Julyati Hisyam; Aline Nikita; Anissa Nurul Chotimah; Jemima Fathima Pasha; Nadila Sahla Mulia (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Weverse is a platform launched by HYBE Corporation in 2019 and has played a central role in facilitating interactions between fans and artists in the Korean music industry (K-pop). Through exclusive access to content, direct communication with artists, and a membership system offering discounts and exclusive content, Weverse has become a "home" for K-pop fans and an important revenue source in the industry's economy. This study uses a qualitative approach with a systematic literature analysis design to explore the impact of Weverse in the K-pop industry, highlighting the importance of this platform in deepening the relationship between artists and fans as well as its contribution to the business model and economy in the Korean music industry.